PENGARUH PEMAHAMAN DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Afrida, Anggrelia; Kusuma, Gumulya Sonny Marcel (Balance : Jurnal Akuntansi dan Bisnis, 2022)
The purpose of this research was to analyze relationship of Understanding, Awareness, Individual Taxplayer Compliance with Taxation Socialization as a moderating variable. Sampling was done by simple random sampling technique to select the respondent. The sample in this research was 100 individual taxplayer at KKP Pratama Palembang Ilir Timur. Data analysis techniques performed by Structural Equation Model with Partial Least Square. The result indicate significant influence understanding on the individual taxplayer compliance and taxation socialization as a moderating variable. Futhermore, it was found that there were no significant influence awareness on the individual taxplayer compliance and taxation socialization as a moderating variable